Heutagogy Based E-Training: Internship Teacher Digital Competence for an Equitable Global Civilization - Faraasyatul, Ghasa; Budi Wiyono, Bambang; Burhanuddin; Muslihati (Journal of Technical Education and Training, 2024)
The development of the digital transformation era has had a major influence on the current occupational fields. The challenges faced by the next generation of the nation are getting bigger; this is also felt by internship teachers (teacher training) who carry out school field introduction programs from universities. Seeing the low output to be able to get the opportunity to become a teacher with a bachelor’s degree in education is the main concern of inequitable global civilization. The aim of the research is to focus on knowing the needs of internship teachers related to digital competence training before they carry out the school field introduction program. The research method used is a mixed method with a total of 160 active students at Brawijaya University who will become internship teachers. The results of the study reveal that the need for the aspect of gaining new competencies is 85%, the development of digital competencies is very high, especially in the aspect of integrating digital pedagogy, and the knowledge aspect is 65% for increasing heutagogy-based e-training experiences. This study concludes that the need for internship teachers for the existence of heutagogy-based e-training is very much needed to realize an equitable global civilization in the era of digital transformation.